2006
DOI: 10.1620/tjem.209.41
|View full text |Cite
|
Sign up to set email alerts
|

Slow Coronary Flow is Associated with Carotid Artery Dilatation

Abstract: Slow coronary flow (SCF) in a normal coronary angiogram is a wellrecognized clinical entity, but its etiopathogenesis remains unclear. Carotid intima-media thickness (CIMT) is a noninvasive marker of atherosclerosis. The aim of this study was to investigate the CIMT and diameter of carotid and coronary artery in relation to SCF. Twenty-four patients with angiographically diagnosed SCF (51 ± 7 years), and 26 agematched subjects with normal coronary flow (NCF) (52 ± 8 years) in the coronary angiography were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
8
2
Order By: Relevance
“…They also found that TIMI frame counts were positively correlated with carotid intima-media thickness and coronary intimal thickness and concluded that SCF might be the results of coronary atherosclerosis, which was the part of systemic involvement. In contrast, Yigit et al (2006) found no difference between the patients with NCF and SCF in terms of carotid intimamedia thickness. They also found that carotid and coronary artery diameters are increased in patients with SCF when compared to those of normal coronary flow and concluded that carotid artery dilatation could be used as an early marker of SCF.…”
Section: Discussioncontrasting
confidence: 63%
“…They also found that TIMI frame counts were positively correlated with carotid intima-media thickness and coronary intimal thickness and concluded that SCF might be the results of coronary atherosclerosis, which was the part of systemic involvement. In contrast, Yigit et al (2006) found no difference between the patients with NCF and SCF in terms of carotid intimamedia thickness. They also found that carotid and coronary artery diameters are increased in patients with SCF when compared to those of normal coronary flow and concluded that carotid artery dilatation could be used as an early marker of SCF.…”
Section: Discussioncontrasting
confidence: 63%
“…This is extreme SCF compared to previous studies 9)13)14). IMT of the carotid arteries in the SCF group increased greater in our results than those of other reports 13)14)20). These findings indicate that our subjects were more severe cases of SCF.…”
Section: Discussioncontrasting
confidence: 62%
“…However, serum neopterin levels did not correlate with the extent of coronary artery ectasia (number of ectatic coronary vessels). Yiğit et al (23) showed that carotid and coronary artery diameters were increased in patients with SCF (without coronary ectasia) as compared to those with normal coronary arteries. Papadakis et al (24) have demonstrated that coronary artery ectasia was associated with diminished coronary flow velocity.…”
Section: Discussionmentioning
confidence: 99%